Analysis of the Implementation of Subsidized Homeownership credit Financing Based on the Concept of Maslahah - Sopingi, Imam; Ririn Tri Ratnasari; Imron Mawardi (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2023)
This research aims to analyze the implementation of subsidized home ownership credit financing based on the concept of Maslahah at Bank Tabungan Negara, branch office in Jombang. The research method employed is a qualitative case study with six techniques for data collection, including the researcher's direct participation with the research subject and conducting direct interviews with key informants from the financing service department. The research findings reveal that subsidized home ownership credit is one form of financing provided to the community to purchase homes, with the support of the government through collaboration with Bank Tabungan Negara, branch office in Jombang. Bank Tabungan Negara, branch office in Jombang, also offers various flexible repayment schemes to its customers. However, this research has limitations, such as its focus on a single location and an inability to describe variations in implementation at other locations. Furthermore, the research findings can have positive implications, particularly in the development of more effective policies and programs that align with the community's needs, by offering repayment options that suit customers' financial conditions.